High-Quality de novo Chromosome-Level Genome Assembly of a Single Bombyx mori With BmNPV Resistance by a Combination of PacBio Long-Read Sequencing, Illumina Short-Read Sequencing, and Hi-C Sequencing - Tang, Min; He, Suqun; Gong, Xun; Lü, Peng; Taha, Rehab H.; Chen, Keping (Frontiers in Genetics, 2021)
The reference genomes of Bombyx mori (B. mori), SilkDB and SilkBase have served as the gold standard for nearly two decades. Their use has fundamentally shaped model organisms and accelerated relevant studies on lepidoptera. However, the current reference genomes of B. mori do not accurately represent the full set of genes for any single strain. As new genome-wide sequencing technologies have emerged and the cost of high-throughput sequencing technology has fallen, it is now possible for standard laboratories to perform full-genome assembly for specific strains. Here, we present a high-quality de novo chromosome-level genome assembly of a single B. mori with nuclear polyhedrosis virus (BmNPV) resistance through the integration of PacBio long-read sequencing, Illumina short-read sequencing and Hi-C sequencing. In addition, regular bioinformatics analyses, such as gene family, phylogenetic and divergence analyses, were performed. The sample was from our unique B. mori species (NB), which has strong inborn resistance to BmNPV. Our genome assembly showed good collinearity with SilkDB and SilkBase and particular regions. To the best of our knowledge, this is the first genome assembly with BmNPV resistance, which should be a more accurate insect model for resistance studies.